126k views
3 votes
Help me
Show all your work

Help me Show all your work-example-1

2 Answers

0 votes
3x+2 (5x-1)=11
3x +10x -2=11
3x+10x=13
13x=13
X=1
User Francesco Ceravolo
by
5.7k points
4 votes
3x + 2y = 11
y = 5x-1
For this case, the first thing you should do is replace the value of y in the first equation.
We have then:
3x + 2 (5x-1) = 11
We rewrite:
3x + 10x-2 = 11
3x + 10x = 11 + 2
3x + 10x = 13
We clear x:
13x = 13
x = 13/13
x = 1
We now substitute the value of x in expression 2:
y = 5 (1) -1
y = 5-1
y = 4

Answer:
The solution to the system of equations is:
x = 1
y = 4
User Ian Bush
by
5.8k points